Plant Layout and Pick‐and‐place Strategies for Improving Performances in Secondary Packaging Plants of Food Products1. (11th July 2012) - Comba, Lorenzo; Belforte, Gustavo; Gay, Paolo
<x xml:space="preserve">Abstract</x> The aim of secondary packaging plants is to pick food products from a conveyor belt and to place them into boxes. The typical configuration of these packaging plants consists of a set of sequential robot stations, performing pick‐and‐place cycles from one conveyor to another parallel one, which transport the products and the boxes to be filled. Depending on the relative movement of the two conveyors, the plant operates in co‐current or counter‐current flow configuration. Undesired perturbations in the product flow rate from its nominal value can lead to critical events, i.e. unpicked product at the end of the first conveyor or not completely filled boxes. Even if the structures of co‐current flow and of counter‐current flow plants are very similar, their behaviour in non‐nominal or perturbed conditions can significantly differ. The aim of this paper is to deeply investigate the behaviour of these two kinds of secondary packaging lines, evaluating their performances in the case of different pick‐and‐place strategies, using discrete events simulation techniques. Results show to which extent the different proposed control strategies can improve the performances of both co‐current and counter‐currents plants and, in particular, how co‐current plant layouts can achieve performances that are equivalent to, or perhaps even better than, those that can be obtained with a counter‐current plant layout, which cannot be freely used because of patent. The simulation tool, control algorithms and results presented can help packaging plant designers for choosing the most appropriate solutions and for properly sizing the plant. Copyright © 2012 John Wiley & Sons, Ltd.